An Exploratory Study on the Adequacy of Internship Program Duration in Medical Colleges of Bangladesh - Noman, Farhana; Arefin, ASM Shamsul; Rahman, Shamima; Chowdhury, Sabbir Ahmed; Asaduzzaman, AKM (Bangladesh Journal of Medical Education, 2021)
The internship period provides the first level of postgraduate medical training and serves as one of the fundamental strides in every doctor’s career. An inadequate internship program in terms of duration, skills and quality may pose serious concerns on the overall healthcare sector. Hence, the aim of this study was to explore the adequacy of the duration of internship program in medical colleges of Bangladesh. Till date, any significant study has not been reported to address the issue. A cross-sectional descriptive study with pre-tested self-administered questionnaires was performed. The study was carried out in 8 medical colleges (4 public and 4 non-government; 4 inside Dhaka and 4 outside). 300 completed questionnaires (250 interns, 50 supervisors) were statistically analyzed with SPSSv20 software. Majority of the interns and teachers voiced that the current duration of One-year Internship Program was inadequate and they further suggested that the duration can be revised to at least a year and half. Further opinions were put forward to modify the community placement duration period from two weeks to at least three weeks as the current duration was also deficient. These findings thus can help the policy makers, medical practitioners and academicians to review the current structure and duration of the internship program in medical colleges of Bangladesh for the betterment of the undergraduate medical education as well as the overall healthcare system. Bangladesh Journal of Medical Education Vol.12(1) 2021: 32-39